Parametric Study on Ducted Micro Wind Energy Harvester - In-Ho Kim; Byeong-Ryong Kim; Yeon-Jae Yang; Seon-Jun Jang (Energies, 2022)
Micro wind energy harvester (MWEH) can provide eco-friendly and sustainable energy for low-power electric devices like wireless sensors. The performance of the wind turbine can be enhanced by applying a duct with a brim. In this work, the characteristic study was performed when the duct is applied to the MWEH through the computational fluid dynamics analysis of the internal and external flow of the duct. The power generation performance for various cases was evaluated using the wind tunnel test. It is confirmed that the ducted MWEH is robust to the change of the wind direction and its performance can be further enhanced by the brim.